Analysis of Factors Affecting Employee Morale in the Technical Implementation Unit Office of the Singosari Revenue Agency, Malang Regency - Amelia Setyawati; Irwan Mulyo Mayanto; Amelia Sugangga; Wasis Rizki Widyanto; Adelia Rahma (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
In order to develop and survive in the industrial world, inter-organizational cooperation is urgently needed which aims to provide positive work vibes. with a positive work atmosphere will have a good impact on work results, and psychologically provide morale to all employees. Morale is characterized by the enthusiasm of employees in carrying out their duties/work. This study used a quantitative explanatory research method to test the relationship between leadership and work motivation on work enthusiasm carried out at the UPTD Singosari Regional Revenue Agency, Malang Regency. In this study the population was all employees of the Department of Revenue, Financial Management and Regional Assets UPTD Singosari Malang Regency. Total population of 28 people. Because the total population is 28 employees, this study uses the census method. The independent variables are leadership (X1) and work motivation (X2). The dependent variable is morale (Y). Researchers used questionnaire data collection techniques, and observation. The data analysis technique used is (1) descriptive statistical analysis (2) validity and reliability test (3) hypothesis test. techniques in this study used descriptive statistics using the Statistical Product Service Solution (SPSS) for Windows version 22 program. From the results of the study it can be stated that leadership and work motivation have a partially significant effect on employee morale. Leadership and work motivation in the Service Office of Revenue, Financial Management and Assets Service Technical Implementation Unit (UPTD) Singosari Malang Regency have a significant influence simultaneously on employee morale. Leadership becomes the dominant influence because the trigger for employee morale is a leadership style that is able to provide comfortable working conditions and can also improve employee welfare